Kestabilan Emosi pada Anak Usia Dini dalam Pengaruh Perkembangan Sosial Agama: Emotional Stability in Early Childhood under the Influence of Social and Religious Development - Mariana, Mariana (Absorbent Mind, 2021)
Instilling education in a child is an absolute necessity so that the child can develop well and optimally, especially Islamic Religious Education (PAI) which aims to develop people who are able to carry out the teachings of the Islamic religion well and perfectly, so that it is reflected in their attitudes and actions. throughout his life in order to achieve happiness in the world and the hereafter. This research aims to examine the influence of emotional stability in early childhood on social and religious development at RA MUSLIMAT NU 085 Pulosari Jambon. This research uses an observational method with a quantitative approach. Respondents in this study were young children registered at RA MUSLIMAT NU 085 Pulosari Jambon and their parents or guardians. Data was collected through direct observation of children's social behavior, as well as through questionnaires given to parents or guardians to assess children's emotional stability. Statistical analysis is used to determine the relationship between emotional stability and children's socio-religious development. It is hoped that the results of this research can contribute to a better understanding of the importance of emotional stability in early childhood in shaping social and religious aspects. The practical implications of this research can be a reference for RA MUSLIMAT NU 085 Pulosari Jambon in designing learning programs that pay attention to aspects of children's emotional stability to support optimal social and religious development.